A re-evaluated taxon: Genetic values and morphological characters support the recognition of the Canary Island juniper of the phoenicea group at a specific level - Romo, Angel; Mazur, Małgorzata; Salvà-Catarineu, Montserrat; Boratyński, Adam (Phytotaxa, 2019)
Analyses based on cone, seed and needle characteristics revealed that J. canariensis Guyot in Mathou & Guyot is distinct from both the Circum-Mediterranean J. turbinata and West-Mediterranean J. phoenicea. The genetic differences between these three taxa, which make up the aggregate of J. phoenicea, are found also at a high level. These data support the recognition of the Canarian juniper at the specific level. A key is proposed, in which taxa of the J. phoenicea aggregate can be distinguished on the basis of morphological traits. The nomenclatural name: Juniperus phoenicea subsp. canariensis, widely employed in the literature, is validly published. Besides we adduce that Juniperus canariensis Knight ex Godron, is not a validly published name, and therefore can not be considered an earlier homonym of J. canariensis Guyot in Mathou & Guyot.